PEMAHAMAN KONSEP MATEMATIS: DARI KOGNISI INDIVIDUAL MENUJU PRAKTIK EPISTEMIK–DISKURSIF - Irmawati Liliana Kusuma Dewi; Cita Dwi Rosita; Marwia Tamrin Bakar (Universitas Swadaya Gunung Jati., 2026)
Mathematical conceptual understanding is a fundamental goal of mathematics education, particularly in higher education where students are required to engage with abstract concepts, formal structures, and relationships among mathematical ideas. However, research consistently indicates that instructional practices tend to prioritise procedural success over the development of deep conceptual understanding. This article aims to systematically synthesise research on undergraduate students’ mathematical conceptual understanding by adopting an epistemic–discursive perspective. A systematic literature review was conducted on Scopus-indexed journal articles published between 2014 and 2024 that focus on higher education mathematics. The findings indicate that mathematical conceptual understanding is constructed through the interaction of mathematical representations, discourse and communication, mathematical reasoning, and epistemic norms embedded in learning environments. The review also reveals that conceptual understanding should not be viewed solely as an individual cognitive attribute, but rather as a practice that develops through students’ participation in formal mathematical activity. Based on this synthesis, the article proposes an integrative conceptual framework that positions mathematical conceptual understanding as an epistemic–discursive practice. This framework is expected to contribute to theoretical advancement and inform future research and instructional design in undergraduate mathematics education.